Dissecting the role of the Hawaiian Skirt gene in the regulation of floral development using suppressor analysis strategy - Jayaweera, Dasuni (2013)
Hawaiian Skirt (HWS) is an F-box gene in Arabidopsis that plays a key role in plant floral organ development. HWS has been identified due to sepal fusion along their basal margins resulting in failure to shed its floral organs (Gonzalez-Carranza et al., 2007). Similar phenotypic characteristics can be seen in the ectopically expressed microRNA miR164 (Mallory et al., 2004; Lauf et al., 2004) and in the double mutants cup-shaped cotyledon 1 cucJ/cuc2 (Aida et at., 1997). Previous studies carried out by Gonzalez-Carranza et al. (unpublished) using genetic crosses between hws-1 and other floral mutants has revealed that HWS may play a crucial role in the microRNA biogenesis. In an effort to identify potential substrates of HWS and to identify the role of HWS in the miRNA pathway, a population of EMS mutagenized hws-1 was used for isolation and characterization of suppressors of hws-l. Screening a number of EMS mutagenized hws-l populations has identified several suppressor lines that are currently under study. From the identified mutants, two lines 43.1 and 80.5 were selected for further characterization analysis. These suppressor lines rescue the distinctive sepal fusion phenotype of hws-l as well as displaying other phenotypic characteristics. Characterization of the suppressor lines has identified that 43.1 is an allele of HST gene, which is involved in miRNA biogenesis, and 80.5 is an allele of AS2 gene, which is an adaxial cell fate determinant. Expression analyses have revealed that loss of HWS gene function leads to the repression of both 43.1 and 80.5. Genetic analyses have also confirmed that loss of HWS gene function results in an upregulation of CUC1 and CUC2 gene expression. The results obtained in this project have shown that HWS is involved in miRNA, adaxial-abaxial and Organ boundary signalling, concluding that HWS may have a wider function in different signalling pathways than previously proposed.